Lattices from totally real number fields with large regulator - Ong, Soon Sheng (2015)
We look for examples of totally real number fields with large regulator and inert small primes inside some families of cyclotomic fields. This problem is motivated by the design of wiretap codes for fast fading Rayleigh channels.